2022
DOI: 10.1038/s41419-022-04628-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ferroptosis in acute kidney injury

Abstract: Acute kidney injury (AKI) is a major public health problem with high incidence and mortality. As a form of programmed cell death (PCD), ferroptosis could be considered as a process of iron accumulation and enhanced lipid peroxidation. Recently, the fundamental roles of ferroptosis in AKI have attracted much attention. The network mechanism of ferroptosis in AKI and its roles in the AKI to chronic kidney disease (CKD) transition is complicated and multifactorial. Strategies targeting ferroptosis show great pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 177 publications
(141 reference statements)
1
44
0
Order By: Relevance
“…In past studies on iron toxicity, features of iron toxicity were found to include accumulation of lipid peroxides, disturbances in iron metabolism, accumulation of ROS and the consumption of GPX4 and system Xc- (a cysteine/glutamate antiporter system). ( Ni et al, 2022 ). Biochemically, ferroptosis mainly includes the consumption of glutathione (GSH) and the decreased activity of GPX4 ( Zheng and Conrad, 2020 ; Obeng, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…In past studies on iron toxicity, features of iron toxicity were found to include accumulation of lipid peroxides, disturbances in iron metabolism, accumulation of ROS and the consumption of GPX4 and system Xc- (a cysteine/glutamate antiporter system). ( Ni et al, 2022 ). Biochemically, ferroptosis mainly includes the consumption of glutathione (GSH) and the decreased activity of GPX4 ( Zheng and Conrad, 2020 ; Obeng, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…TECs undergo various types of programmed cell death (PCD) including apoptosis, pyroptosis, necroptosis, and ferroptosis (64)(65)(66)(67). Upon sensing local tissue injury, resident and infiltrating inflammatory cells in the kidney promote TEC PCD by producing and releasing large amounts of inflammatory cytokines and activating various pathway proteins, leading to TEC detachment, tubular occlusion, and tubular inactivation.…”
Section: Immune Cells Promote Various Types Of Programmed Cell Deaths...mentioning
confidence: 99%
“…Several novel therapeutic agents that inhibit necroptosis have already shown efficacy in experimental studies, and human translation appears to be promising [13 && ]. Ferroptosis, a distinct form of nonapoptotic irondependent cell death now well described in AKI, is characterized primarily by intracellular accumulation of labile, catalytic iron, with subsequent lipid peroxidation, membrane rupture and cell death [12,15,16]. Targeted inhibition of ferroptosis via widely available lipophilic antioxidants and iron chelators are achieving promising preliminary results.…”
Section: Alterations In Tubule Cell Deathmentioning
confidence: 99%